Diagnosis of Bacterial Vaginosis in Females with Vaginal Discharge using Amsel’s Clinical Criteria and Nugent Scoring - Shireen Rafiq,Nuzhat Nauman ,Amna Tariq,Samina Jalali (Journal of Rawalpindi Medical College, 2015)
Background: To determine the frequency of bacterial vaginosis in female patients with complaint of vaginal discharge and to evaluate the accuracy of Amsel’s clinical criteria taking Nugent criteria as gold standard. Methods: In this descriptive study female patients of a reproductive age group presenting with a complaint of abnormal vaginal discharge were included. A routine gynaecological speculum examination was performed. Vaginal samples were obtained using two vaginal swabs. Colour, consistency and odour of vaginal discharge was also noted. Amine test was performed (Whiff test) by adding 10% KOH to vaginal secretion to determine if the vaginal discharge gave off a fishy odour and wet mount was examined under microscope for presence of clue cells. Morphotypes were scored as average number . Total number of lactobacilli + Gardeneralla vaginalis + Mobiluncus were quantified and scored. A score of more than 7 was considered as a positive sign for bacterial vaginosis. Nugent scoring system was considered as the gold standard for the diagnosis of BV, and accordingly sensitivity, specificity, positive predictive value and negative predictive value of Amsel’s criteria were determined. Results: The frequency of bacterial vaginosis was 42.16% by gram’s staining. The sensitivity and specificity of Amsel’s clinical criteria was 86.4% and 95.2%. Positive and negative predictive value was 85.3% and 95.6% respectively. Clue cells had the highest specificity. Conclusions: Bacterial vaginosis was found in a higher proportion in symptomatic female patients with vaginal discharge. Amsel’s clinical criteria was found to be useful but inferior in comparison to gram’s staining for the diagnosis of bacterial vaginosis.